Efektivitas Penyuluhan Kesehatan Sekolah terhadap Peningkatan Pemahaman Anemia pada Remaja Putri: The Effectiveness of School-Based Health Education on Improving Knowledge of Anemia among Adolescent Girls - Metana Puspitasari; Nur Mahmudah; Linda Jana Sintaningtyas; Muhammad Daffa Qory; Aura Veranisyah Sudarto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Anemia is a prevalent public health problem among adolescent girls who are undergoing rapid growth and have increased iron requirements. This condition is often worsened by unbalanced dietary habits, restrictive dieting, and limited knowledge about daily nutritional needs and anemia prevention. This community service activity aimed to improve adolescents' understanding of anemia through a school-based health education program. The education was delivered interactively through visual presentations and was accompanied by pre-test and post-test assessments to measure changes in knowledge. A total of 113 students participated in the program. Data were analyzed to evaluate differences in knowledge levels after the intervention. The results showed an increase in the mean knowledge score from 89 to 98, with a statistically significant difference under the Wilcoxon test (p <0,001). Most participants demonstrated improved scores after the session, indicating the effectiveness of the educational method. The program's success was supported by the delivery of communicative materials, the use of easy-to-understand visual media, and strong participant engagement. This activity highlights the important role of health education in improving health literacy among adolescent girls and suggests its potential as a promotive and preventive strategy to reduce anemia. Similar educational programs are recommended for continued implementation to foster long-term anemia-prevention behaviors and support improved health outcomes for future generations.